STRATEGIC HUMAN RESOURCE PLANNING BASED ON OPTIMIZATION OF EMPLOYEE COMPETENCE: SYSTEMATIC LITERATURE REVIEW - Asrizal, Asrizal; Sopiah, Sopiah (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
The purpose of this SLR is to examine how human resource development is implemented in the workplace. The PICO (Population, Intervention, Comparison, and Outcome) handbook is used as the methodology for this study. Data sources for 2018–2024 are from Google Scholar, Connected Paper, Science Direct, and the Publish or Perish application. After 114 journal findings were collected, 30 journals were selected for evaluation after data reduction using inclusion and exclusion criteria. The findings of this literature assessment show how important strategic human resource planning is to increase productivity so that both businesses and employees (HR) benefit from strategic human resource planning. The results of optimizing HR competencies have an impact on increasing work ethics which will drive the success of achieving company goals. For the reasons of increasing and optimizing HR competencies, companies need to carry out strategic HR planning. The Prism Diagram is used to illustrate the selection and filtering of previous studies. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram is a tool used in research with a focus on systematic reviews and meta-analyses